“PNP slows down” – linearly-reduced whole body joint velocities and altered gait patterns in polyneuropathy - Walz, Isabelle D.; Waibel, Sarah; Lippi, Vittorio; Kammermeier, Stefan; Gollhofer, Albert; Maurer, Christoph (Frontiers in Human Neuroscience, 2023)
This is a provisional file, not the final typeset article Methods 20 PNP patients (61±14 years) and a matched healthy control group (CG, 60±15 years) performed TUG at i) preferred and ii) fast movement speed, and iii) while counting backward (dual-task). We recorded TUG duration [s] and extracted gait-related parameters (step time [s], step length [cm], and width [cm]) during the walking sequences of TUG and calculated center of mass (COM) velocity (represents gait speed [cm/s]) and joint velocities [cm/s] (ankles, knees, hips, shoulders, elbows, wrists) with respect to body coordinates during walking; we then derived mean joint velocities and ratios between groups.Across all TUG conditions, PNP patients moved significantly slower (TUG time, gait speed) with prolonged step time and shorter steps compared to CG. Velocity profiles depend significantly on group designation, TUG condition, and joint. Correlation analysis revealed that joint velocities and gait speed are closely interrelated in individual subjects, with a 0.87 mean velocity ratio between groups.We confirmed a PNP-related slowed gait pattern. Interestingly, joint velocities in the rest of the body measured in body coordinates were in a linear relationship to each other and to COM velocity in space coordinates, despite PNP. Across the whole body, PNP patients reduce, on average, their joint velocities with a factor of 0.87 compared to CG and thus maintain movement patterns in terms of velocity distributions across joints similarly to healthy individuals. This down-scaling of mean absolute joint velocities may be the main source for the altered motor behavior of PNP patients during gait and is due to the poorer quality of their somatosensory information.German Clinical Trials Register (DRKS), Identifier: DRKS00016999.